The Hazards of Malnutrition in Early Infancy - Ratna Indrawati (Indonesian Pediatric Society Publishing House, 2019)
Severe protein calorie malnutrition is often accompanied by vitamin A deficiency and intercurrent infections. These three conditions have a synergistic action on each other. The younger the infant, the more severe are the hazards of nutritional deficiency. Severe malnutrition in early infancy results in: • Direct hazards to the infant consisting of: • Retardation of physical development. • Retardation of brain development with subsequent impairment of learning ability. • Decreased resistance against infections. • PCM is a predisposing factor to diarrhoea, with aggravated the malnutrition. • Blindness due to vitamin A deficiency.